2017 9th International Congress on Ultra Modern Telecommunications and Control Systems and Workshops (ICUMT) 2017
DOI: 10.1109/icumt.2017.8255162
|View full text |Cite
|
Sign up to set email alerts
|

Near optimal linear-service oriented resource allocation strategy for LTE networks

Abstract: Abstract-Extensive research efforts are being attracted towards resource allocation in LTE networks. However, from the resource allocation perspectives, linear services such as Digital TV programs have been scarcely studied. In fact, for end-users requesting linear services, the maximization of the the number of users served is much important goal than maximizing the overall capacity of the network. In this paper, linear services oriented resource allocation strategy is proposed. The goal of the proposed algor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…However, since eMBMS is not yet widely deployed, this work considers a UC transmission for the BB network. Indeed, it was shown that UC could achieve significantly high coverage rates with a proper allocation of available resources [38]. In contrary to the previous works in [13,[28][29][30]] where a grid model was used to describe the BB network, a more accurate PPP is used here to model BSs positions.…”
Section: Contributions and Methodologymentioning
confidence: 99%
“…However, since eMBMS is not yet widely deployed, this work considers a UC transmission for the BB network. Indeed, it was shown that UC could achieve significantly high coverage rates with a proper allocation of available resources [38]. In contrary to the previous works in [13,[28][29][30]] where a grid model was used to describe the BB network, a more accurate PPP is used here to model BSs positions.…”
Section: Contributions and Methodologymentioning
confidence: 99%
“…BB networks covers large service areas divided into relatively small cells with relatively low transmission power. In each cell, service delivery is conventionally carried out using the Unicast (UC) mode in which the spectrum resource is shared and distributed to users [6]. With unicast, BB networks are very efficient to individualize the service delivery but may suffer from overload issues when a large number of users are demanding for high bandwidth services [7].…”
Section: A Linear Mobile Tv Servicementioning
confidence: 99%
“…However, non was originally designed for linear services. In this work, the algorithm we proposed in [8] is used for allocating resource blocks to users served by UC.…”
Section: B Resource Allocation Schemementioning
confidence: 99%
“…Stochastic geometry tools with a Poisson Point Process (PPP) are used to model the broadband network. The resource allocation scheme proposed in [8] is adopted here to make the best use of spectral resources. We then analyze a set of design parameters affecting power efficiency of the hybrid network.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation